Analisis Risiko Berdasarkan Aspek Operasional Dan Pengendalian Internal Pada Salah Satu SPPG Di Kota Bandung - Shahnaz Azka Handini; Erlangga Putra Kosasih; Faridah Nur Setyaningtyas; Aristanti Widyaningsih; Rozmita Dewi Yuniarti (Pasca Sarjana UKI, 2026)
The implementation of the Free Nutritious Meal Program (MBG) through the Nutrition Fulfillment Service Units (SPPG) entails high operational complexity and exposes the program to various risks, particularly in the operational and internal control dimensions. This study aims to analyze the risk profile of one SPPG in Bandung City and to identify mitigation strategies necessary to support effective program governance. A descriptive qualitative approach supported by simple quantitative analysis (mixed approach) was employed. Data were collected through structured interviews with the Head of SPPG, the Operational Field Officer (PLO) for Nutrition, the PLO for Finance, and program beneficiaries. Risk analysis was conducted using the Likelihood-Impact Matrix approach in accordance with ISO 31000:2018. Results indicate that among the 48 operational risks identified, seven are classified as medium risk, relating to location selection transparency, labor verification, beneficiary data synchronization, food production alignment, and procurement processes; the remaining 41 are low risk, with no high-risk items detected. In the internal control dimension, eight medium risks were identified spanning control environment, internal risk assessment, control activities, and monitoring. Beneficiary satisfaction surveys further confirmed high satisfaction levels with program service quality. This study concludes that SPPG governance is functioning reasonably well; however, strengthening internal controls, data integrity, human resource capacity, and system digitalization are essential for program sustainability.